Theoretical and experimental study for temperature distribution and flow profile in all water evacuated tube solar collector considering solar radiation boundary condition. (15th January 2017) - Essa, Mohamed A.; Mostafa, Nabil H.
Highlights: A three dimensional transient numerical simulation for the flow inside evacuated tube solar collector with storage tank considering irradiance. The numerical simulation temperature was validated with experimental results from others with average relative errors ranging from 4.2 to 7.8% at specific points inside the tube. The variation of solar radiation intensity and angles of incidence were considered in this study. A visualization experiment for the flow inside the evacuated tube was handled to emphasize the findings from the numerical study. The structure of the flow inside the tube is affected by the solar radiation variation in intensity and incidence and formed a helical shape streamlines inside the tube which is very clear around solar noon time. Abstract: This study investigated a three-dimensional transient numerical simulation of water flow inside evacuated tube solar collector connected to a storage tank. It validates the distribution of the temperature inside the evacuated tube with experimental data from other studies. Variation of the solar radiation intensity and angle of incidence were discussed. The Effect of radiation variation on temperature contours and flow circulation inside the tube was discussed as well. The simulation results showed an agreement with the experimental data by an average relative error ranging from 4.2 to 7.8% at the validated points of temperature measurements. The structure of the flow inside the tube is affected by the variation of solar radiation in intensity and incidence angle. This variation causes the streamlines inside the tube to form two different shapes. The first shape is linear profile beside the top surface of the tube upwards and inclined with the tube. The second shape is a helical one inside the tube declared at the end of the simulation time and was confirmed by a vision experiment. The helical shape is formed due to the synchronous motion of the sun rays on the outer surface of the tube and the motion of the flow upwards. This is clear when the buoyancy velocity increases around the solar noon time.